2014
DOI: 10.1017/s0272263114000187
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Designs in Sentence Processing Research

Abstract: Since the publication of Clahsen and Felser's ( 2006 ) keynote article on grammatical processing in language learners, the online study of sentence comprehension in adult second language (L2) learners has quickly grown into a vibrant and prolifi c subfi eld of SLA. As online methods begin to establish a foothold in SLA research, it is important that researchers in our fi eld design sentence-comprehension experiments that adhere to the fundamental principles of research design typical of sentence processing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
136
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 40 publications
1
136
0
2
Order By: Relevance
“…Marsden, Thompson, and Plonsky (2018b) represents another recent methodological synthesis with parallels to the present study. Their review, like ours, focused on the use of one particular elicitation procedure, self-paced reading, which has likewise been the subject of a number of debates concerning construct validity as well as what might constitute appropriate implementation and design (e.g., Keating and Jegerski, 2015;Roberts, 2016). Marsden et al's results indicated that the features of self-paced reading tasks vary widely.…”
Section: Methodological Transparency and Rigormentioning
confidence: 99%
“…Marsden, Thompson, and Plonsky (2018b) represents another recent methodological synthesis with parallels to the present study. Their review, like ours, focused on the use of one particular elicitation procedure, self-paced reading, which has likewise been the subject of a number of debates concerning construct validity as well as what might constitute appropriate implementation and design (e.g., Keating and Jegerski, 2015;Roberts, 2016). Marsden et al's results indicated that the features of self-paced reading tasks vary widely.…”
Section: Methodological Transparency and Rigormentioning
confidence: 99%
“…The SSH is considered a mainstream theory of L2 psycholinguistics, in fact potentially the main promoter of the surging interest in L2 processing since the early 2000s (cf. Keating & Jegerski, 2015). Because it most directly corresponds to claims of processing proper, its main thesis can be applied within multiple theories of linguistic representation.…”
Section: Psycholinguistics Brings New Research Techniques and Methodsmentioning
confidence: 99%
“…The self-paced reading (SPR) test was administered after the CMTs and used 16 items from the CMT-Listen 7 , with eight context-stimulus matches and eight mismatches, counterbalanced as described above for the CMT tests. Half the items were followed by Yes/No comprehension questions to increase the likelihood that participants focused on meaning (see Keating & Jegerski, 2015) 8 . The answers to the questions only depended on a lexico-semantic feature (but not verb stems) and not on inflectional morphology.…”
Section: Stimulus (Habitual): Quand Patrick Quittait La Maison Il Vomentioning
confidence: 99%